Sublethal effect and molecular responses of Musca domestica to cinnamon extracts - Akram Alghamdi; Muhammad Nadir Naqqash; Nimra Batool; Muhammad Asif Farooq; Ahmed Noureldeen; Hadeer Darwish; Attalla F. El-kott; Salama A. Salama; Yasser Rabea Elmarassi (The Science of Nature, 2025)

Cyto-genotoxic assessment of bisphenol P through expression of DNA damage/repair genes in MDBK cell line - Muhammad Muddassir Ali; Samra Afzal; Maryam Javed; Imran Rashid; Furqan Awan; Asad Ullah; Tanveer Majeed; Hadeer Darwish; Ahmed Noureldeen; Jawaher Albaqami; Khalid Mehmood (In Vitro Cellular & Developmental Biology - Animal, 2025)

Impact of field evolved resistance on biological parameters of non-targeted Aedes aegypti populations - Nimra Batool; Muhammad Asif Farooq; Waqar Jaleel; Ahmed Noureldeen; Akram Alghamdi; Hadeer Darwish; Naif H. Ashri; Muhammad Nadir Naqqash (Ecotoxicology, 2025)

Iron oxide nanoparticles and light intensity modulate biomass, antioxidant capacity and anti-leishmanial activity in callus cultures of Artemisia scoparia - Reema Yousaf; Mubarak Ali Khan; Afzal Raza; Ambreen; Huma Ali; Hadeer Darwish; Khadiga Alharbi; Najla Amin T. Al Kashgry; Ahmed Noureldeen (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Formulation of tizanidine hydrochloride–loaded provesicular system for improved oral delivery and therapeutic activity employing a 23 full factorial design - Amira Mohamed Mohsen; Hadeer Ahmed El-Hashemy; Abeer Salama; Asmaa Badawy Darwish (Drug Delivery and Translational Research, 2023)
Tizanidine hydrochloride (TZN) is one of the most effective centrally acting skeletal muscle relaxants. The objective of this study is to prepare TZN-loaded proniosomes (TZN-PN) aiming at enhanced oral delivery and therapeutic activity. TZN-PN were prepared by coacervation phase separation method. The developed vesicles were characterized via entrapment efficiency percentage (EE%), vesicular size (VS), and zeta potential (ZP). A 2 3 full factorial design was employed to attain an optimized TZN-PN formulation. The optimized TZN-PN were further characterized via in vitro release study and transmission electron microscopy (TEM). In vivo rotarod test was employed for determination of the muscle relaxant activities of rats and levels of GABA and EAAT2 were detected. The developed TZN-PN exhibited relatively high EE% (75.78–85.45%), a VS ranging between (348–559 nm), and a ZP (−26.47 to −59.64). In vitro release profiles revealed sustained release of TZN from the optimized TZN-PN, compared to free drug up to 24 h. In vivo rotarod study revealed that the elevation in coordination was in the following order: normal control < free TZN < market product < TZN-PN (F6). Moreover, the optimized TZN-PN exhibited significant elevated coordination activity by 39% and 26% compared to control group and market product group, respectively. This was accompanied with an elevation in both GABA and EAAT2 serum levels. Thus, it could be concluded that encapsulation of TZN in the provesicular nanosystem proniosomes has enhanced the anti-nociceptive effect of the drug and consequently its therapeutic activity. Graphical abstract